Fish and fishery products - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1995)
Fish and fishery products: composition, nutritive properties and stability edited by A Ruiter 1995 400pp ISBN 085198 927 6 Hbk price UKL55.00 CAB International, Wallingford, Oxon OX10 8DE, UK